Monopolar 250–500 Hz language mapping: Results of 41 patients - Verst, S.M.; de Aguiar, P.H.P.; Joaquim, M.A.S.; Vieira, V.G.; Sucena, A.B.C.; Maldaun, M.V.C. (Clinical neurophysiology practice, 2019)
•Monopolar mapping is effective for cortical and subcortical language areas.•250–500 Hz stimulation parameters are adequate and safe for speech testing.•It may improve resection rate of infiltrating tumor areas involving the speech area. To determine whether high-frequency 250–500 Hz monopolar stimulation is effective for mapping cortical and subcortical language structures during brain tumor resection. Using high-frequency monopolar stimulation, we mapped the speech areas of 41 awake patients undergoing brain tumor resection in the dominant hemisphere, subject to risk of lesions in the cortical and subcortical speech tracts. Patients were tested for object naming, semantic and other language tasks. Mapping was positive in 22 out of 41 patients. Nine patients presented clinical worsening immediately after surgery. Only one patient did not recover after the 30-day follow-up. Nineteen patients showed negative mapping for language tracts, none of whom exhibited worsening of symptoms at the final evaluation. The applied method showed 89% sensitivity and 56% specificity rates. The applied method was effective in identifying cortical and subcortical speech areas during the surgical resection of brain tumors. Determining whether monopolar high-frequency stimulation is effective for language mapping is important, since it may be very effective in infiltrating tumor areas and nearby edema region.